The Influence of Religiosity On Consumer Behavior in Purchasing Halal Label Cosmetics - Fadhila Tianti Mudi Awalia; Setiawan Bin Lahuri (Ijtihad, 2021)
The development of halal lifestyle trends is now making the increased demand for halal products, including cosmetics. A product that is used almost every day by women. However, there are still many cosmetics in circulation that are not halal certified.This research conducted at UNIDA Gontor for Girls where the population consisted of students, lecturers and staff. A structure questioner is designed with 5-scale Likert to collect primary research data. From 260 respondents, 245 questionnaires are selected from the proportional stratified random sampling method. Multiple regression analysis is used as statistical techniques for the purpose of data analysis using statistical package for social science (SPSS) version 21 to process data and answer the problem formulation.The results of this study reveal that religiosity influences consumer purchasing behavior towards halal labeled cosmetics, and the higher the level of one’s religiosity, the more  consistent he will behave in accordance with religious teachings.  And explains the relationship of 5 dimensions of religiosity (ideology, practice, knowledge, experience and consequence) to consumer behavior on purchasing halal cosmetics simultaneously and partially, and the five dimensions of religiosity significantly influence consumer purchasing behavior towards halal labeled cosmetics.